2023
DOI: 10.3390/ijms241612840
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience in Treatment of Patients with Non-Small-Cell Lung Cancer with BRAF or cMET Exon 14 Skipping Mutations

Abstract: BRAF and cMET exon 14 skipping are rare mutations of NSCLC. The treatment sequence in these cases for the first and second line is not clear. An international registry was created for patients with advanced NSCLC harboring BRAF or cMET exon 14 skipping mutations, diagnosed from January 2017 to June 2022. Clinicopathological and molecular data and treatment patterns were recorded. Data on 58 patients, from eight centers across five countries, were included in the final analysis. We found that 40 patients had th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Additionally, previous real-world data found that patients with the BRAF V600E mutation achieved a 78% ORR, with a mOS similar to our findings. However, this study included only 17 evaluable patients, so the results should be interpreted with caution ( 53 ). Hence, treatment choices, including the potential use of ICI combinations or BRAF TKIs, should therefore be personalized, taking into account each patient’s unique profile and the specific line of therapy being considered.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous real-world data found that patients with the BRAF V600E mutation achieved a 78% ORR, with a mOS similar to our findings. However, this study included only 17 evaluable patients, so the results should be interpreted with caution ( 53 ). Hence, treatment choices, including the potential use of ICI combinations or BRAF TKIs, should therefore be personalized, taking into account each patient’s unique profile and the specific line of therapy being considered.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, more research needs to be carried out on the recurrence of ICI-associated cardiotoxicity such as randomized trial investigation. In addition, investigation is needed into the incidence of ICI-associated cardiotoxicity in women versus men, since women generally have a higher risk of autoimmune diseases and are underrepresented in clinical trials due to this fact [14,19,35,39,63,65,[82][83][84][91][92][93]. As we have searched in the literature, we have found only two cases reported about myo-and pericarditis as complications of immune checkpoint inhibitors [94,95].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment beyond progression is well defined in the therapy of NSCLC with specific agents such as tyrosine kinase inhibitors in special situations [ 24 , 25 ], but it is still not completely understood in treatment with IO [ 26 ]. The resistance mechanisms for this particular nivolumab plus ipilimumab combination are still not understood and may involve different pathways for IO, such as tumor microenvironment (TME) [ 27 ], as well as for chemotherapy, such as adaptive resistance mechanisms [ 28 ].…”
Section: Discussionmentioning
confidence: 99%